3(n-1)=5n+3(-2n)

Simple and best practice solution for 3(n-1)=5n+3(-2n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(n-1)=5n+3(-2n) equation:


Simplifying
3(n + -1) = 5n + 3(-2n)

Reorder the terms:
3(-1 + n) = 5n + 3(-2n)
(-1 * 3 + n * 3) = 5n + 3(-2n)
(-3 + 3n) = 5n + 3(-2n)

Remove parenthesis around (-2n)
-3 + 3n = 5n + 3 * -2n

Multiply 3 * -2
-3 + 3n = 5n + -6n

Combine like terms: 5n + -6n = -1n
-3 + 3n = -1n

Solving
-3 + 3n = -1n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add 'n' to each side of the equation.
-3 + 3n + n = -1n + n

Combine like terms: 3n + n = 4n
-3 + 4n = -1n + n

Combine like terms: -1n + n = 0
-3 + 4n = 0

Add '3' to each side of the equation.
-3 + 3 + 4n = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 4n = 0 + 3
4n = 0 + 3

Combine like terms: 0 + 3 = 3
4n = 3

Divide each side by '4'.
n = 0.75

Simplifying
n = 0.75

See similar equations:

| 2x+5+10x-12=90 | | x(3y+2c)= | | (26+7)*3= | | 1+2t=16 | | 2x-14+3(1x-1)=13 | | 275=25x-.5x^2 | | y=(20-x)-(20-y) | | C=0.19m+32.99 | | 5u+2=-18 | | y=11+1x | | 2x-20=y | | 5.95+.19x=5.83 | | 2j+14=5x+50 | | 500+22w=1204 | | g(x)=5x+-1 | | -8x^2-16x+64=0 | | N*6+2=8 | | 0.4(X+3)-0.6(X+3)=-0.2-0.6 | | 7+3(1x-4)-10=-45 | | 2x-3y=12.5 | | 12x+8=-120(18x+5) | | 8(3x-3)=4(6x+9) | | 5x+18=12x+9 | | T=r+(k+3)w | | 45(200-y)+30y=7125 | | 2x^2-8x-48=0 | | R(4+5)=60 | | 4u-11=69 | | 10x+5-8+3x-5x+1=14 | | 500+22=1204 | | k(u)=2*u+2 | | 7+10a=32 |

Equations solver categories